1998
DOI: 10.1530/eje.0.1390101
|View full text |Cite
|
Sign up to set email alerts
|

Testicular seminoma in a patient with a constitutively activating mutation of the luteinizing hormone/chorionic gonadotropin receptor

Abstract: A white man who had been diagnosed, 35 years previously at the age of 27 months, to have precocious puberty, was later determined to have familial male-limited precocious puberty (FMPP), on the basis of his family history, increased serum testosterone, prepubertal concentrations of follicle stimulating hormone and luteinizing hormone, and Leydig cell hyperplasia. Recently, this diagnosis was confirmed by molecular genetic analysis that demonstrated the presence of a heterozygous constitutive activating mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 19 publications
1
16
0
1
Order By: Relevance
“…DNA sequencing of the affected tissue identified the Asp564Gly mutation, which was also present in the patient's peripheral blood cells; this is in stark contrast to the Asp578His patients, whose testicular mutation did not appear in their peripheral blood cells. Previously, a case of testicular germ cell tumour in an FMPP patient caused by an activating mutation Asp578Gly was published [10]. This patient was diagnosed at the age of 27 months and he developed a testicular seminoma 35 years later.…”
Section: Discussionmentioning
confidence: 99%
“…DNA sequencing of the affected tissue identified the Asp564Gly mutation, which was also present in the patient's peripheral blood cells; this is in stark contrast to the Asp578His patients, whose testicular mutation did not appear in their peripheral blood cells. Previously, a case of testicular germ cell tumour in an FMPP patient caused by an activating mutation Asp578Gly was published [10]. This patient was diagnosed at the age of 27 months and he developed a testicular seminoma 35 years later.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an FMPP patient with testicular seminoma was reported (322). The occurrence of these relatively rare disorders could be attributed to chance but could also be the effect of continuous stimulation by increased levels of androgens.…”
Section: Future Directionsmentioning
confidence: 99%
“…Also, high intratesticular testosterone was found to suppress spermatogonial proliferation in the radiationdamaged rat testis [85]. Other reports have established that elevated serum testosterone levels increased the risk for testicular germ cell tumors in human subjects [86,87]. On the other hand, a number of studies have shown that isoflavones may act within the seminiferous epithelium to impact spermatogenesis without concomitant endocrine changes [88,89].…”
mentioning
confidence: 94%